English: Pembingkaian Adegan Romansa dalam Serial Film dengan Rasio Vertikal - Erina Adeline Tandian (Fakultas Film dan Televisi - Institut Kesenian Jakarta, 2026)
Movies first appeared in the late 1800s using a horizontal 4:3 (1.33:1) aspect ratio. Over time, film aspect ratios have undergone various changes to meet needs. In today's digital era, many films and videos have emerged with vertical formats, adapting to the shape of smartphones as one of the streaming media. This article aims to determine how framing is used in several Indonesian vertical screen format film series, also known as microdramas, especially romantic dramas that often highlight intimate scenes between two people. This study uses qualitative research methods, with observation technique or textual analysis on visual scenes from several Indonesian microdramas. The results of the analysis indicate that the vertical aspect ratio in romance series can restrain intimacy between characters. This disruption in framing is also attempted to be overcome by several creative strategies, one of which is rotating the camera position ninety degrees to accommodate medium two shot.